Capital structure based on earnings alignment as a transmission mechanism between sustainable growth and firm value - Rahman, Faisal Riza; Wahyudi, Sugeng; Pangestuti, Irene Rini Demi (Edelweiss Applied Science and Technology, 2026)
This study aims to develop and empirically test the Capital Structure–Earnings Alignment (CaSEA) model as an integrated framework linking sustainable growth and firm value through capital structure efficiency and debt-servicing capacity. Using panel data from 228 manufacturing firms listed on the Indonesia Stock Exchange (2019–2024), the research employs panel data regression and STATA-based analysis. The CaSEA index, combining the Debt-to-Equity Ratio (DER) and Times Interest Earned (TIE), measures leverage efficiency and earnings alignment. The results reveal that sustainable growth positively and significantly influences firm value, both directly and indirectly through CaSEA. Higher CaSEA values indicate improved capital discipline, reduced financial distress risk, and stronger market valuation. Sustainable growth enhances internal financing capacity and earnings coverage, which, when aligned with capital structure efficiency, leads to higher firm value. The study extends the Trade-Off Theory and Signaling Theory by demonstrating the mediating role of earnings alignment in the growth–value relationship. Practical implications suggest that managers in emerging markets should integrate profitability, financing policy, and payment capability within growth strategies to sustain firm value and long-term financial resilience.